Dampak Pandemi Covid-19 Terhadap Frekuensi Konsumsi Pangan Rumah Tangga di Kota Kendari - Elmiati Elmiati; Haji Saediman; Wa Ode Yusria (Jurnal Ilmiah Membangun Desa dan Pertanian, 2022)
The study aimed to determine the consumption frequency of every food type, determine the frequency of eating meals on the day before and during the Covid-19 pandemic, and assess the impact of the pandemic on both the consumption frequency of each food and on the frequency of eating meals in a day. The research was conducted in Kendari Municipality, Southeast Sulawesi Province as it has the highest number of Covid-19 cases in the province. The study was undertaken from February to November 2021. The respondents were 80 people taken from household consumers who were shopping at two traditional markets. Data analysis was done using descriptive statistics based on the results of scoring for each variable, Wilcoxon Signed-Rank Test, and McNemar Test. The study results showed that the consumption frequency of rice was in the very high category, while corn, sago, and cassava were in the low category. The frequency of consumption of vegetables is very high, while milk, instant noodles, and fruit are each quite high. The frequency of consumption of fish and eggs is high, while the meat is quite high. The types of food whose consumption levels differed significantly before and during the pandemic were fish, cassava, eggs, and fruit. Meanwhile, on the frequency of eating meals in a day, the majority of respondents ate three times a day, and the frequency of eating did not show any difference before and during the pandemic.